2021
DOI: 10.1093/jpepsy/jsab073
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Empathic Accuracy: Associations With Type 1 Diabetes Management and Familism

Abstract: Objective To (1) test associations between parents’ empathic accuracy for their adolescents’ positive and negative emotions and adolescents’ physical and mental health (HbA1c, diabetes self-care, and depressive symptoms) in a predominantly Latinx sample of adolescents with type 1 diabetes and their parents, and (2) explore how familism values were associated with parent empathic accuracy and adolescent physical and mental health in this population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…These findings indicate that the correspondence in overall affect and affective synchrony that has been documented during interactions between parents and infants and young children (e.g., Bornstein et al, 2021 ; Feldman, 2007 ; Sallquist et al, 2010 ) is also present in early to mid-adolescence. Previous reviews have highlighted the importance of examining affective synchrony in parent–adolescent exchanges (e.g., Lougheed, 2020 ) and the current study is one of the first examples to do so (see also Main et al, 2021 ). Further, the current findings suggest that VMR is a potentially important tool to capture affect in parent–adolescent dyads in real time.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These findings indicate that the correspondence in overall affect and affective synchrony that has been documented during interactions between parents and infants and young children (e.g., Bornstein et al, 2021 ; Feldman, 2007 ; Sallquist et al, 2010 ) is also present in early to mid-adolescence. Previous reviews have highlighted the importance of examining affective synchrony in parent–adolescent exchanges (e.g., Lougheed, 2020 ) and the current study is one of the first examples to do so (see also Main et al, 2021 ). Further, the current findings suggest that VMR is a potentially important tool to capture affect in parent–adolescent dyads in real time.…”
Section: Discussionmentioning
confidence: 93%
“…Preliminary construct validity of this task was supported, as well, considering medium positive associations between parent and adolescent affect and small negative associations between adolescent in-task affect and their own internalizing and externalizing symptoms. VMR has been implemented in studies of adult couples ( Rohrbaugh et al, 2009 ), but this is one of the first studies to provide evidence that parents, and most importantly adolescents, can provide affect ratings on a moment-to-moment basis while viewing a video of themselves (see also Main et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on empathic accuracy, which refers to the accuracy of parents' empathy toward their child's condition, revealed that parents may show poor empathic accuracy for their child's negative emotions and suggested that enhancing parents' empathic accuracy is crucial to promoting mental and physical health of children with T1DM (Main et al, 2022 ). In general, the same educational content is to be used for patients with T1DM and their parents, but identifying the differences in their educational needs would enable the development of tailored education.…”
Section: Introductionmentioning
confidence: 99%
“…Empathy is one of the most essential resources for parents of children with a chronic disease [ 15 ]. When parents are more attuned to their children's thoughts and feelings, adolescents with chronic diseases demonstrate greater self-care and fewer depressive symptoms [ 15 ].…”
Section: Introductionmentioning
confidence: 99%